2018
DOI: 10.1007/s11856-018-1791-0
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Loewy factorizable algebraic ODEs and Hayman’s conjecture

Abstract: In this paper, we introduce certain n-th order nonlinear Loewy factorizable algebraic ordinary differential equations for the first time and study the growth of their meromorphic solutions in terms of the Nevanlinna characteristic function. It is shown that for generic cases all their meromorphic solutions are elliptic functions or their degenerations and hence their order of growth are at most two. Moreover, for the second order factorizable algebraic ODEs, all the meromorphic solutions of them (except for on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Ng and Wu [20] investigated the second-order nonlinear Loewy factorizable algebraic ordinary differential equations (ODEs) and showed that the conjecture proposed by Hayman in 1996 holds for some certain second-order ODEs. Although many methods for constructing solutions of ordinary differential equations have made enormous progress [21], higherorder nonlinear ordinary differential equations are rarely investigated, especially analytical solutions.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Ng and Wu [20] investigated the second-order nonlinear Loewy factorizable algebraic ordinary differential equations (ODEs) and showed that the conjecture proposed by Hayman in 1996 holds for some certain second-order ODEs. Although many methods for constructing solutions of ordinary differential equations have made enormous progress [21], higherorder nonlinear ordinary differential equations are rarely investigated, especially analytical solutions.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Remark 1. Using this method, one can prove that for a large class of n-th order autonomous algebraic ODEs, their meromorphic solutions must be elliptic or degenerate elliptic (see [31]). The method fails if there is a positive Fuchs index and hence one cannot conclude the finiteness of the number of Laurent series.…”
Section: Step 2 Clunie's Lemmamentioning
confidence: 99%
“…These are the only meromorphic functions which satisfy the addition formulae. They are also the only meromorphic solutions of certain non-linear complex differential equations (see [10], [4], [5], [6], [19] and [12]).…”
Section: Introductionmentioning
confidence: 99%